Effect of time of day and physical exercise on inflammatory biomarkers in athletic horses - Aragona, Francesca; Giannetto, Claudia; Piccione, Giuseppe; Arfuso, Francesca; Arrigo, Federica; Costa, Antonino; De Caro, Salvatore; Cannuli, Antonio; Fazio, Francesco (Frontiers in Veterinary Science, 2025)
IntroductionThe present study aimed to investigate the effect of time of day and physical exercise on some inflammatory biomarkers (white blood cell count-WBCs, leukocyte subpopulation CD4 + and CD8 + cells, total proteins, Interleukins IL-6, IL-1β and Tumor Necrosis Factor TNFα) in trained saddle horses.MethodsBlood samples were collected from 10 horses before, immediately (following 5 min) and 1 h after the training session in the morning (am) and afternoon (pm).Results and discussionStatistical analysis showed increasing value of WBCs immediately and 1 h after exercise (p < 0.01: p < 0.01) at am compared to rest. Lower CD4 + oncentration was observed immediately and 1 h after exercise (p < 0.01; p < 0.01) at pm compared to rest and decreased levels 1-h post-exercise at pm compared to am (p < 0.001). CD8 + exhibited significant lower value at pm compared to am at each time point (before: p < 0.01; immediately: p < 0.01; 1 h after: p < 0.001). IL-6 showed increasing value post-exercise at pm (p < 0.01). IL-6 and IL-1β levels were markedly elevated at pm compared to am at each time point (p < 0.0001; p < 0.0001; p < 0.0001). This information is essential for formulating suitable training regimens, considering performance in connection to possible daily risk for infection, illness, and inflammation to which the horse may be vulnerable.